Generating useful images for medical applications from the Visible Korean Human - Park, Jin Seo; Jung, Yong-Wook; Lee, Jun Won; Shin, Dong Sun; Chung, Min Suk; Martin Riemer; Heinz Handels (Computer methods and programs in biomedicine, 2008)
For the Visible Korean Human (VKH), a male cadaver was serially ground off to acquire the serially sectioned images (SSIs) of a whole human body. Thereafter, more than 700 structures in the SSIs were outlined to produce detailed segmented images; the SSIs and segmented images were volume- and surface-reconstructed to create three-dimensional models. For outlining and reconstruction, popular software (Photoshop, MRIcro, Maya, AutoCAD, 3ds max, and Rhino) was mainly used; the technique can be reproduced by other investigators for creating their own images. For refining the segmentation and volume reconstruction, the VOXEL-MAN system was used. The continuously upgraded technique was applied to a female cadaver's pelvis to produce the SSIs with 0.1mm sized intervals and 0.1mm x 0.1mm sized pixels. The VKH data, distributed worldwide, encouraged researchers to develop virtual dissection, virtual endoscopy, and virtual lumbar puncture contributing to medical education and clinical practice. In the future, a virtual image library including all the Visible Human Project data, Chinese Visible Human data, and VKH data will hopefully be established where users will be able to download one of the data sets for medical applications.
Keywords: Computer Simulation; Diagnostic Imaging; Female; Humans; Imaging, Three-Dimensional; Korea; Male; User-Computer Interface; Visible Human Projects